Reliability and construct validity of DASS 21 using Malay version: a pilot study / Kartini Kasim ... [et al.] - Kasim, Kartini; Shamsuddin, Norin Rahayu; Wan Salleh, Wan Zulkipli; Kamaruddin, Kardina; Mohamed Ramli, Norazan (2015)
A pilot study was conducted to examine the internal consistency reliability and construct validity for the Malay-version of the Depression Anxiety Stress Scale-21 (DASS 21).A total of 349 participants were involved that consisted of academic and administration staff from a local university in Kedah. The specificity of the individual DASS 21 items was assessed from self-administeredquestionnaires. Our results indicated a satisfactory internal consistency based on the Cronbach’s alpha values. The depression, anxiety and stressvalues are 0.92, 0.78 and 0.84, respectively, which was in the range of good to excellent indication.. The factor loading analysishas also shown a good factor loading for most items (0.30 to 0.79) which explains the theoretical construct of this instrument. These result suggested that the Malay-version DASS 21 is reliable and valid for assessing depression, anxiety and stress in other institutions.